Comparison of the sensitivity and cross-reactivity between heat-killed and formalin-killed cells during the development of indirect competitive ELISA for the detection of Salmonella Typhimurium (Journal of Environmental Bioremediation and Toxicology, 2014)
Newer discovery of Salmonella strains warranted the development of newer ELISA system. Theaim of this works is to develop a sensitive and simple indirect ELISA for the detection ofSalmonella Typhimurium using formalin- and heat-killed cells as immunogens. The parameters ofthe resultant calibration curve for the formalin-killed cells (FKC) were minimum absorbance of0.101± 0.011, maximum absorbance of 2.804± 0.020, slope parameter of 1.197, while c, theconcentration that results in 50% response was 4.22 x 106 CFU/ml. The LOD and LOQ were19,300 and 52,700 CFU/mL, respectively. The parameters of the typical calibration curve forheat-killed cells (HKC) were minimum absorbance of 0.115± 0.013, maximum absorbance of2.810± 0.021, slope parameter was 1.441, while c, the concentration that results in 50% responsewas 2.15 x 106 CFU/ml. The LOD and LOQ were 47,100 and 123,000 CFU/mL, respectively.Antibody raised to FKC was twice the sensitivity and approximately ten times the linear rangecompared to antibody raised to HKC. Antibody produced from formalin-killed cells exhibitedlower cross reactivity than heat-killed cells. The results of this work could open new avenues onoptimization of antigen preparation for maximal sensitivity of the developed polyclonal antibody.
Keywords: indirect ELISA, Salmonella Typhimurium, formalin-killed, heat-killed, four parameter logistic equation